1999
DOI: 10.1039/a900189a
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of carbonyl carbon 13C NMR chemical shifts, IR absorption frequencies and rate coefficients of nucleophilic acyl substitutions. A novel explanation for the substituent dependence of reactivity

Abstract: Rate coefficients of nucleophilic acyl substitutions, carboxylate carbon 13 C NMR chemical shift values and ν(C᎐ ᎐ O) frequencies of several series of aryl and acyl substituted aryl acetates or alkyl benzoates have been investigated. An increasing electron-withdrawal by the acyl or aryl substituents results in higher reaction rates, upfield 13 C NMR chemical shifts and higher frequencies of the C᎐ ᎐ O stretching. Good correlations are observed for the log k versus δ C (C᎐ ᎐ O) plots. The increase of the reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 24 publications
6
72
0
Order By: Relevance
“…the rates observed for a series of structurally related compounds. [22] They observed that the IR absorption frequencies of the ester carbonyl group unexpectedly increased with the reaction rate. Therefore, esters bearing EWGs showed higher frequencies (higher double-bond character), which contradicted the tacit assumption of increased electrophilicity of the carbonyl carbon.…”
Section: Initial Rates Of the Lbadh-catalyzed Ht Of Ketones 2 B-hmentioning
confidence: 99%
“…the rates observed for a series of structurally related compounds. [22] They observed that the IR absorption frequencies of the ester carbonyl group unexpectedly increased with the reaction rate. Therefore, esters bearing EWGs showed higher frequencies (higher double-bond character), which contradicted the tacit assumption of increased electrophilicity of the carbonyl carbon.…”
Section: Initial Rates Of the Lbadh-catalyzed Ht Of Ketones 2 B-hmentioning
confidence: 99%
“…They were selected to cover a broad range of Hammett's σ ‐values, which is a classical method to estimate electron density of aromatic systems depending on the aromatic substituents. However, to determine electron densities, NMR spectroscopy is the accepted method of choice . It was expected that the electron‐density of the arylsulfonamide‐moiety could influence the reactivity of the oxirane system.…”
Section: Resultsmentioning
confidence: 99%
“…These simpler derivatives enabled study of a wider selection of substructures across diverse physicochemical property space demonstrating the importance of both electronic and steric factors to the rate of ester hydrolysis. Additionally, the 13 C NMR shift of the ester carbonyl carbon was measured as previous reports have illustrated a good correlation between ester hydrolysis rates and the corresponding 13 C NMR shifts [16,17]. The methyl ester hydrolysis rates/ 13 C NMR shift (measured) correlation for this new data set is shown in Fig.…”
Section: Relationship Between 13 C Nmr Shifts and Methyl Ester Hydrolmentioning
confidence: 97%